PWE-136 Bowel Cancer Screening Non Responders: What Can Be Done to Increase Uptake in Men From Lower Socioeconomic Groups?. (17th August 2016) - Scott, J; Elton, P; Lipscomb, G; Paynter, S; Scott, J; Hill, N
Abstract : Introduction: In the 2006 UK Bowel Cancer Screening Pilot, uptake levels were around 60%. 1 As of 2014, in Bolton, the uptake rate amongst men in the lowest deprivation quintiles was less than 50%. 2 This study aims to aims to discover the factors that influence Bowel Cancer Screening Non-Responders to not complete their kit; and to explore interventions to increase uptake in this population. Methods: Between Sept 2012 and Sept 2013, 131 male BCS non-responders were exposed to incremental GP endorsement interventions of increasing intensity (letter, telephone call and the offer of a face to face interview). 10 non-responders were resistant to both letters and telephone calls, but consented to an interview. The interviews were semi-structured, and explored BCS attitudinal barriers and "Cues to Action" found in a review of the current literature. Analysis was performed using an inductive, grounded theory approach. 3 Results: Interview analysis yielded 32 attitudinal and interventional themes. Common attitudinal themes included "the Poo Taboo", "Masculinity" and "the NHS Disconnect". Most participants felt embarrassed to talk about or handle their faeces (the Poo Taboo). Some felt that screening tests, particularly invasive tests, weren't "manly" (Masculinity). A few declined the test, because they distrusted the local hospital or the NHS in general (the NHS Disconnect). Health literacy was low in this group, the majority knew very little about Bowel Cancer and Bowel Cancer Screening. Improving knowledge and health education were thought to be important interventional "Cues to Action". Conclusion: Bowel Cancer Screening Non-Respondence is a complex and multifactorial problem with no "silver bullet" solution. The subject of Bowels and Bowel Cancer Screening requires further normalisation. Strategies such as endorsement from Friends and Family; and GP group educational events were thought to be important tools for improving BCS perceptions, behaviour and ultimately response. References: 1 Bowel Cancer Screening Pilot. http://www.cancerscreening.nhs.uk/bowel/pilot-2nd-round-evaluation.pdf 2 Bolton Health Matters. http://www.boltonshealthmatters.org/sites/default/files/PHIT-Report-10-Bowel-Cancer-Screening-in-Bolton.pdf 3 Crabtree B, Miller W, eds. Doing qualitative research . 2nd ed. Newbury Park, Calif: Sage; 1999. Disclosure of Interest: None Declared